"Fulfilling His Needs, Not Mine": Reasons for Not Talking About Painful Sex and Associations with Lack of Pleasure in a Nationally Representative Sample of Women in the United States. Issue 12 (21st September 2019) - Carter, Allison; Ford, Jessie V.; Luetke, Maya; Fu, Tsung-chieh (Jane); Townes, Ashley; Hensel, Devon J.; Dodge, Brian; Herbenick, Debby
Abstract: Introduction: Although much research has examined correlates of pain during sex, far less research has examined why women have sex despite having pain and why they avoid telling their partner. Aim: The purpose of our study was to examine women's reports of painful sex, including location of pain, whether they told their partner, factors associated with not disclosing their pain, and their reasons for not disclosing. Methods: We used data from the 2018 National Survey of Sexual Health and Behavior, a probability-based online survey of 2, 007 individuals ages 14 to 49 years. We limited our sample to adult women who reported a sexual experience that was painful in the past year (n = 382; 23.2%). The primary outcome in quantitative analyses was whether women told their partner they experienced pain during sex. Associations with social identities and sexual health were explored via logistic regression. Those who did not tell their partner about painful sex were asked why; their accounts were coded and analyzed qualitatively. Main Outcome Measure: Women were asked, "To what extent was this sexual experience physically painful for you?" Those who reported any pain were asked, "Did you tell your partner that you were in pain during sex?" and, if applicable, "Why didn't you tell your partner that you were in pain during sex?" Results: Of those reporting pain during sex, most said it was "a little painful" (81.6%) and occurred at the vaginal entrance (31.5%), inside the vagina (34.4%), or at or around the cervix (17.4%). Overall, 51.0% (n = 193/382) told their partner about their pain. Adjusting for age and wantedness, women who reported little or no event-level sexual pleasure had nearly 3-fold greater odds of not telling a partner about painful sex (adjusted odds ratio = 3.24; 95% CI, 1.43–7.37). Normalizing painful sex, considering pain to be inconsequential, prioritizing the partner's enjoyment, and gendered interactional pressures were the predominant themes in women's narratives. Clinical Implications: Providers should ask about painful sex, if the woman continues intercourse despite pain, and how she feels about this as a means of assessing any sexual and social pressures. Strengths & Limitations: Strengths include the use of social theory in nationally representative survey research to examine how contextual factors influence sexual health, but experiences were largely limited to heterosexual interactions. Conclusion: Many women do not discuss painful sex with their partners, lack of pleasure is significantly more likely among this group, and gender norms and cultural scripts are critical to understanding why.